Effect of Concrete Strength on Shear Capacity of Reinforced High-Strength Concrete Continuous Beams without Web Reinforcements - Bamo Ahmed Hasan; Jalal Ahmed Saeed (Advances in Civil Engineering)
In order to evaluate the shear strength and behavior of high-strength concrete beams without web reinforcing, eight high-strength continuous concrete beams with cross sections of 200 mm by 300 mm were cast and tested to failure. The ultimate load-carrying capability and shear behavior are presented. The applicability of the Sudheer et al. equations and ACI 318M-14 is examined. In addition, the effects of the compressive strength (fc′) and shear span to effective depth ratio (a/d) on the shear strength and behavior of HSRC beams without stirrups are also studied. 63 MPa, 78.8 MPa, 85.9 MPa, and 92 MPa were the concrete’s compressive strengths, while 2.41 and 3.33 were its shear span to effective depth ratios. There were two equal spans of continuous beams, and at each span, they were evaluated under a single-point load. It was found that with increasing compressive strength, the failure load was increased. But the deflection did not affect it significantly. While increasing, (a/d) led to a decrease in failure load but increased deflection. It was also found that both ACI 318 M-14 and Sudheer et al. equation were more conservative.